Investigation of physical, chemical and technological properties of Mercenaria stimpsoni in the process of storage - Natalia M. Kupina (Известия ТИНРО)
Changes of physical, chemical, and organoleptic parameters during storage of cut and raw frozen bivalve Mercenaria stimpsoni are considered. Portion of its edible parts is estimated as 12-15 % of total weight, depending on age, and waste (shells and liver) takes 70-75 % of the total weight. The meat of Mercenaria stimpsoni is distinguished by low protein content (8.5-9.8 %), low fat content (0.7-1.0 %), and low caloric value (46-52 kcal) in any area and any season. The tissues of its foot and mantle have proteins with the content of essential amino acids higher than in the reference FAO/WHO protein and biologically active taurine, as well, and proteins of the muscle have lowered portion of the myofibrillary and sarcoplasmatic proteins and heightened portion of the connective tissue proteins. Mercenaria stimpsoni is capable to alive retention up to 16 days under the temperature 2-4oC. The concentration of the proteinogenic amino acids, taurine and anserine does not change in the process of storage, but the content of myofibrillary protein decreases in 15-20 %, and the content of dilacerated proteins increases in 2.4 times. Mercenaria stimpsoni caught at Primorye coast is safe for human consumption by content of toxic elements and radioactive nuclides in its muscle tissue and viscera.